2022
DOI: 10.1186/s41927-021-00238-8
|View full text |Cite
|
Sign up to set email alerts
|

Small vessel vasculitis and dry gangrene secondary to combined CTLA-4 and PD-1 blockade in malignant mesothelioma

Abstract: Background Malignant pleural mesothelioma (MPM) is a rare and aggressive tumour with an overall poor prognosis. In October 2020, first line treatment with the PD-1 antagonist nivolumab and the CTLA-4 antagonist ipilimumab for unresectable disease was FDA approved—the first approved treatment regime since 2004. Interim analyses from the phase 3 CHECKMATE-743 study shows improvements in overall survival. Skin-related toxicities are the most commonly reported any-grade treatment-related adverse ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Earlier, vasculitic neuropathy was reported in two mesothelioma patients treated off-label with anti-PD-1 monotherapy ( 10 , 11 ), and a retrospective pharmacovigilance study identified 10 cases of neuropathy and two of vasculitis among 23 patients with mesothelioma experiencing n-irAEs ( 12 ). In addition, there is one recently published report of cutaneous vasculitis, reminiscent of patient 1, in a mesothelioma patient treated with combined nivolumab and ipilimumab ( 13 ). Herein, definite or possible vasculitic neuropathy was observed in nearly half (3/7) of mesothelioma patients included in a large cohort of patients with n-irAEs, and we did not observe it in any other cancer type, leading to the speculation of a possible association between mesothelioma, ICIs, and vasculitic neuropathy, that future studies need to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, vasculitic neuropathy was reported in two mesothelioma patients treated off-label with anti-PD-1 monotherapy ( 10 , 11 ), and a retrospective pharmacovigilance study identified 10 cases of neuropathy and two of vasculitis among 23 patients with mesothelioma experiencing n-irAEs ( 12 ). In addition, there is one recently published report of cutaneous vasculitis, reminiscent of patient 1, in a mesothelioma patient treated with combined nivolumab and ipilimumab ( 13 ). Herein, definite or possible vasculitic neuropathy was observed in nearly half (3/7) of mesothelioma patients included in a large cohort of patients with n-irAEs, and we did not observe it in any other cancer type, leading to the speculation of a possible association between mesothelioma, ICIs, and vasculitic neuropathy, that future studies need to confirm.…”
Section: Discussionmentioning
confidence: 99%
“…The predominant types include giant cell arteritis, aortitis, or central nervous system vasculitis (23,40). Reported smaller vessels vasculitides include leukocytoklastic vasculitis, type III cryoglobulinemia, granulomatosis with polyangiits and eosinophilic granulomatosis with polyangiitis (EGPA) (19,23,(44)(45)(46). Evaluation for systemic involvement is required and often systemic steroids are initiated (19).…”
Section: Dermatologic-rheumatologic Diseasesmentioning
confidence: 99%